Armas de fogo e suicídios - Daniel Cerqueira; Danilo Santa Cruz Coelho; Marcelo Fernandes; Jony Pinto Junior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– There is virtually a consensus that the ratio of suicides committed with guns to total suicides is the best way to indirectly measure gun ownership across different locations. However, such a proxy is not accurate for any locality with low population density in view that suicides are rare events. To circumvent this issue, we exploit the socioeconomic characteristics of the suicide victims so as to come up with a novel proxy for gun ownership. We assess our indicator using suicide micro-data from the Brazilian Ministry of Health between 2000 and 2010.
Keywords: C15; C51; I18; 330; crime; firearm; fixed effects; logit; regularization; suicides; violence